Parental Cancer: Acceptance and Usability of an Information Booklet for Affected Parents - Melchiors, Leslie; Geertz, Wiebke; Inhestern, Laura (Frontiers in Psychology, 2022)
Background Parents affected by cancer are confronted with challenges such as communicating with their children about the disease and dealing with changes in their parental role. Providing appropriate information could support affected parents and their children. Still, high-quality and information booklets are rare. Therefore, we developed an information booklet for affected families. The study aims are: (1) investigating the acceptability and usability of the information booklet, (2) determining parental information needs, and (3) collating suggestions for implementation. Finally, we adapted the booklet according to the findings. Methods We interviewed five experts in psychosocial care of parental cancer and nine affected parents using a semi-structured interview guideline. Participants received the developed booklet after giving the consent to participate. Interviews on acceptability and usability of the booklet and information needs were conducted about 1 week after receiving the booklet. The interviews were analyzed using structuring content analysis. Results (1) Experts and parents reported that the information booklet addresses the experiences of affected families and that the content combination makes it useful in an unprecedented way indicating both acceptance and usability. (2) Following dimensions were identified as information needs: (a) communication, (b) support offers, (c) children’s disease understanding and needs, (d) organization of family life, (e) competence in parenting, and (f) sources of additional information material. (3) The booklet should be handed out personally by, e.g., healthcare professionals and might be accompanied by a personal counseling. Minor adaptations on language and content were conducted based on the findings. Conclusion Indicated acceptance and usability of the developed information booklet for parents with cancer suggest a low-threshold, basic support for affected families and health professionals. The diverse parental information needs are covered. The long-term effects of the booklet, e.g., on the use of psychosocial support offers, parental self-efficacy and psychological distress will be quantitatively investigated.